Some Identities on the High-Order -Euler Numbers and Polynomials with Weight 0 - Jongsung Choi; Hyun-Mee Kim; Young-Hee Kim (Abstract and Applied Analysis)
We construct the th order nonlinear ordinary differential equation related to the generating function of -Euler numbers with weight 0. From this, we derive some identities on -Euler numbers and polynomials of higher order with weight 0.